Coping strategies among nursing staff at a university hospital - José Ricardo Ferreira da Fonseca; Ana Lúcia Siqueira Costa; Diandra Sabrina Seixas Coutinho; Raquel da Costa Gato (Rev Rene)
Objective: to evaluate the association of coping strategies and characteristics of nursing professionals at a universityhospital. Methods: cross-sectional, quantitative study, with 92 professional nursing of an inpatient unit of a universityhospital. To evaluate them, Problems Coping Scale Mode was used, and the analysis was through the Spearman correlationcoefficient and the Mann-Whitney test. Results: a strategy focused on the problem was the most used, women seek morethe strategy focused in religious practice than men (p=0.017). The age (p=0.031), individual income (p=0.049) and workinghours (p=0.027) had also significantly correlation with the dimensions of the scale. Conclusion: socio-demographiccharacteristics are associated with coping strategies and may influence the choice of the individual for coping strategy.